ANATOMY OF THE RENAL SYSTEM VASCULAR SYSTEM - Vaxobov Lutfullo (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information about the circulatory system of the kidney system and the vascular system of the organs near the kidney. As urologists treat patients with kidney system, we need to know the anatomy of its organs well.